Survei Tingkat Skill Related Fitness Pada Siswa Siswi Sekolah Dasar Negeri Fase C Gugus 1-5 di Kecamatan Sukun Kota Malang - Satria, Asmo Tegar Nada; Wiguno, Lokananta Teguh Hari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research aims to identify the level of skill related fitness in Phase C students at SDN Gugus 1-5 in Sukun District, Malang City. This type of research is descriptive quantitative with survey methods. The research population was 2,124 students, with a sampling technique using proportionate stratified random sampling. The sample used was 96 students, consisting of 48 boys and 48 girls. Data collection was carried out in accordance with the Indonesian Student Fitness Test (TKSI) Phase C. Based on overall data analysis, the results obtained for each test were as follows: 40 meter running test. The test results showed that the frequency of 77 students was dominant in the very poor category. For the 8 x 10 meter suttle run test, the test results showed that the frequency of 44 students was dominant in the good category. The child ball test results show that the frequency of 25 students is dominant in the very good category. The dynamic balance test results show that the frequency of 44 students is dominant in the good category. The vertical jump test results show that the frequency of 43 students is dominant in the poor category. Meanwhile, the hand touch reaction test results showed that the frequency of 39 students was dominant in the poor category. From these results, the school and its PJOK teachers need to provide learning programs to improve the physical fitness of their students during and outside class hours.